2020
DOI: 10.1007/s42452-020-2599-1
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant responses against aluminum metal stress in Geitlerinema amphibium

Abstract: In the current scenario, aluminum is one of the major metals that cause environmental pollution and has ill impact on organism health. As around 40% of bauxite deposits of India are available in Odisha, aluminum toxicity in the soil has impacted as an intimidating problem of Odisha. This aluminum metal pollution is regarded as a primary factor for limiting crop productivity in acidic soils of tropic and subtropic countries. The presence of a high degree of aluminum metal in the soil leads to loss of beneficial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 37 publications
2
4
0
Order By: Relevance
“…In this study, our data con rmed a reduced protein content in the Cd-treated cells, which was signi cantly elevated in the low dose gamma radiation primed strains, even after the Cd treatment. These results are well supported by previous ndings (Pradhan et al 2020c;Achary et al 2008;Kováčik and Dresler 2018;Golari et al 2018). Several mechanistic investigations have suggested that ROS induces cell death post heavy metal stress (Zhao et al 2020;Chokshi et al 2020).…”
Section: Discussionsupporting
confidence: 91%
“…In this study, our data con rmed a reduced protein content in the Cd-treated cells, which was signi cantly elevated in the low dose gamma radiation primed strains, even after the Cd treatment. These results are well supported by previous ndings (Pradhan et al 2020c;Achary et al 2008;Kováčik and Dresler 2018;Golari et al 2018). Several mechanistic investigations have suggested that ROS induces cell death post heavy metal stress (Zhao et al 2020;Chokshi et al 2020).…”
Section: Discussionsupporting
confidence: 91%
“…In this study, our data con rmed a reduced protein content in the Cd-treated cells, which was signi cantly elevated in the low dose gamma radiation primed strains, even after the Cd treatment. These results are well supported by previous ndings (Pradhan et al 2020c;Achary et al 2008;Kováčik and Dresler 2018;Golari et al 2018). Several mechanistic investigations have suggested that ROS induces cell death post heavy metal stress (Zhao et al 2020;Chokshi et al 2020).…”
Section: Discussionsupporting
confidence: 91%
“…The estimation of protein content and antioxidant defence enzymes such as CAT, APX, GPX, GSR, and SOD were quanti ed as previously described by Pradhan et al (Pradhan et al 2020a;Pradhan et al 2020c).…”
Section: Estimation Of Protein and Antioxidant Enzymesmentioning
confidence: 99%
“…The aberrant accumulation of H 2 O 2 is liable for oxidative stress [29,30] and inflammatory reactions, which can contribute to the development of pathological conditions, such as cancer, diabetes, and cardiovascular diseases [31]. The rapid decomposition of H 2 O 2 subsequently generate hydroxyl radicals ( • OH) that initiate lipid peroxidation and cellular damage [32].…”
Section: Discussionmentioning
confidence: 99%